Pengukuran Produktivitas Ozon Sebagai Oksidator Senyawa Organik Pencemar - Wanda Suwarno; David Andrio; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Ozone is one of strong oxidant agent with potential oxidation value of 2,08 eV. Character of ozone are sharp-smelling and an unstable form composed of three oxygen atoms (O). Since 1990s, the using of ozone developed very wide and rapidly where ozone is used for drinking water treatment and wastewater treatment, sterilization of food and equipment, preservatives and odor removal. Ozone known with radical hydroxyl (OH•) which easily react with organic or inorganic compounds. In this research aims to calculate and measure the productivity of ozone generator with brand ozonizer WS88011i. This research used oxygen from the ambient air as the feed gas. Productivity of ozone generators analysis by iodometry refers to the International Ozone Association Standarized Ozone Procedure Iodometric Method 001/1996. The results showed the productivity of ozonizer WS88011i based on corona discharge method can produce dosage of ozone with range 0,239 - 0,264 g/hour.Keywords: ozone, ozone generator, productivity of ozone